Apples, oranges and lemons: Public sector debt statistics in the 21st century - Mike Seiferling (Financial Innovation, 2020)
In both academic research and policymaking, public sector debt and debt-to-GDP ratios are relied on for a multitude of important economic, political and socioeconomic decisions, especially as public sector balance sheets expand to an unprecedented size in the midst of the 2019-2020 COVID pandemic. The reliance on available data from reputable sources often overlooks the question of whether the denominator in this ratio is accurately measured or how well the denominator is understood by the audience interpreting it. Building on past work in international financial statistics, and making use of a unique and newly created dataset on media reporting of public sector debt, the purpose of this article is to examine the quality, accuracy, interpretation and overall meaningfulness of public sector financial statistics. The main findings suggest that i) most of the world's governments still do not seem to feel sufficient pressure to voluntarily provide comprehensive financial statistics based on well-defined modern methodological frameworks and ii) high profile financial statistics, which are reported, have become increasingly numerous and complicated, making it difficult for non-experts to know which is most appropriate in the context of their analysis.
Keywords: H1; H3; H6; H7; G3; M4; F5; 650; Public finance statistics; Economic measurement; Public debt; Government debt; Politics of statistics